2014
DOI: 10.1088/0169-5983/46/4/041410
|View full text |Cite
|
Sign up to set email alerts
|

Oblique cross-waves in horizontally vibrated containers

Abstract: The excitation of subharmonic waves on the free surface of a horizontally vibrated, rectangular container of liquid is considered and the properties of threshold patterns are obtained and discussed. These waves are generally quasiperiodic and oblique (not aligned with the container walls). The parametric forcing mechanism generated by the harmonic oscillatory bulk flow is assumed to dominate over that associated with harmonic surface waves and a linear theory recently developed by the authors [Perez-Gracia et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…The results of Sec. IV C 2 agree with recent theoretical work on cross waves [20,35,36,45] in predicting a primary Hopf bifurcation to modulated (quasiperiodic) solutions. The results of that section go further in, among other things, predicting the destruction of these modulated solutions in a saddle-node heteroclinic bifurcation (less often, in a standard heteroclinic bifurcation).…”
Section: Comparison With Experimentssupporting
confidence: 87%
See 1 more Smart Citation
“…The results of Sec. IV C 2 agree with recent theoretical work on cross waves [20,35,36,45] in predicting a primary Hopf bifurcation to modulated (quasiperiodic) solutions. The results of that section go further in, among other things, predicting the destruction of these modulated solutions in a saddle-node heteroclinic bifurcation (less often, in a standard heteroclinic bifurcation).…”
Section: Comparison With Experimentssupporting
confidence: 87%
“…Purely dissipative coupling produces the opposite, a region of pitchfork bifurcations centered at ν = 0 with Hopf bifurcations outside of this, in accordance with Eqs. (42) and (45). Perturbations of these conservative and purely dissipative cases are similar, but with asymmetrically located A more complete bifurcation picture is shown in Fig.…”
Section: General Forcing Phasementioning
confidence: 77%
“…They concluded that the cross-waves were oblique in nature, with angles between 50° and 80°. Similar findings related to the obliqueness of the cross-waves were reported in Pérez-Gracia et al (2013, 2014). It was further concluded that the subharmonic cross-waves form because of the parametric instability caused by the combination of primary harmonic surface waves and oscillatory bulk flow of the fluid.…”
Section: Introductionsupporting
confidence: 90%
“…The cross-wave instability is commonly observed in wavemaker experiments [8,110] when sufficient forcing is applied. As indicated by its name, the instability produces waves that are oriented (nearly, but not completely [119,120,123]) perpendicular to the forcing axis and to the directly forced harmonic waves. They were first described by Faraday [43], in an experiment with a partially submerged vibrating plate, as forming a series of apparently permanent ridges projecting outward "like the teeth of a coarse comb".…”
Section: Cross-wavesmentioning
confidence: 99%